Meta analysis of women politician portrait in mass media frames - Sazali, Hasan; Basit, Lutfi (Penerbit Universiti Kebangsaan Malaysia, 2020)
In every discourse on women, the issue of gender equality and how the involvement of the media in the struggle for gender equality always arises. This issue occurs not only in countries that are not yet democratically established, but also in countries that have had established democratic systems. This study aims to describe the portrait of women politicians in a mass media frame. The portrait was examined based upon the results of previous studies using meta-analysis methods. The unit of analysis used in this study is written documents obtained from the result of a research on women politicians and mass media in the form of journal articles and research reports taken purposively by adjusting them to the research theme. This study uses quantitative data analysis with percentages and qualitative data analysis for data obtained from the results of a narrative study of the researches that were found. The results show that the media in America, Europe, Africa, and Asia, with different levels of democratic establishment, have treated female politicians in the same way as male politicians, by framing female politicians negatively and applying standards that are detrimental to women. Women politicians are presented by the media in terms of gender and femininity instead of ability, strength of vision, and competence in politics. Portraits of women in the frame of the mass media are still blurred in America, Europe, Africa and Asia.